2013
DOI: 10.1007/s00330-013-2821-2
|View full text |Cite
|
Sign up to set email alerts
|

Perfusion CT allows prediction of therapy response in non-small cell lung cancer treated with conventional and anti-angiogenic chemotherapy

Abstract: • Perfusion CT has the potential of providing in vivo information about tumour vasculature. • CT depicts early and specific perfusion changes in NSCLC under anti-angiogenic drugs. • Specific therapeutic effects of anti-angiogenic drugs can be detected before tumour shrinkage. • Early perfusion changes can help predict therapeutic response to anti-angiogenic treatment. • Perfusion CT could be a non-invasive tool to monitor anti-angiogenic treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 25 publications
5
45
0
Order By: Relevance
“…Previous studies have also documented that higher MVD is associated with higher blood flow and blood volume values [23]. Regarding the assessment of therapy response, Tacelli et al determined whether CT perfusion can depict early perfusion changes in lung cancer treated with anti-angiogenic drugs [24]. The authors could disclose that patients treated with conventional chemotherapy with bevacizumab had a significant perfusion reduction, as compared to patients without anti-angiogenic treatment [24].…”
Section: Imaging Techniquesmentioning
confidence: 95%
“…Previous studies have also documented that higher MVD is associated with higher blood flow and blood volume values [23]. Regarding the assessment of therapy response, Tacelli et al determined whether CT perfusion can depict early perfusion changes in lung cancer treated with anti-angiogenic drugs [24]. The authors could disclose that patients treated with conventional chemotherapy with bevacizumab had a significant perfusion reduction, as compared to patients without anti-angiogenic treatment [24].…”
Section: Imaging Techniquesmentioning
confidence: 95%
“…17,18 Functional parameters, derived from the assessment of peak tumor enhancement over time in the tissue during the CTP scan, give information about blood volume (BV), blood flow (BF), and mean transit time (MTT) within the network of tumoral neovascularity, as well as the rate of abnormal leakage into the extracellular space, due to the vascular hyperpermeability in the abnormal neovessel wall. 5,19 One of the first applications for the assessment of lung lesions with CTP was pulmonary nodules, particularly in comparison with 18 F-fluoro-2-deoxy-D-glucose positron emission tomography/ CT (PET/CT). 20 Cutoff values have been defined for several CTP parameters to differentiate benign from malignant pulmonary nodules, with lower perfusion index (PI) and higher BF and BV obtained in malignancy.…”
Section: Results: According To Biopsy 37 Patients Had Nsclc (22 Adenmentioning
confidence: 99%
“…Fraioli et al 19,36 demonstrated a significant difference in BF and BV in LCC patients for partial response and progressive disease. Although we did not address therapeutic effects, the results of our study indicate that both histological subtype and tumor volume likely should be taken into account when assessing tumoral treatment response using CTP.…”
Section: Nguyen-kim Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…CTp was shown to be effective for response assessment of antiangiogenic chemotherapy of NSCLC. 104 Moreover, Wang et al 105 showed that CTp can predict early tumour response and overall survival, mentioning, however, that image quality was good or moderate in only 68.2% of the cases.…”
Section: Mr Spectroscopy Mr Spectroscopy (Mrs) That Ismentioning
confidence: 99%